Brain Based Teaching Model as Transformation of Learning Paradigm in Higher Education - Sesmiarni, Zulfani (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
Brain -based teaching model is a new paradigm that can facilitate students in optimizing student learning by the functioning the brain as a whole. Lessons are held today assume that all students equally so that learning provide the same services to each student in the class. With this model, the students are given different stimulation according to their abilities and needs. Base on brain learning theory -based teaching, the learning should pay attention to the five needs of the brain in general. The fifth factor is the need for a sense of comfort, the need for interaction, the need for knowledge, the need for the activity and the need for self-reflection. All these needs will be connected if the lecturers able to present emotional learning, social learning, cognitive learning, physical learning and teaching reflection.Â Key Word : Instrucetional, Brain Based teaching, Learning.Copyright Â© 2015 by Al-Talim All right reserved